2017
DOI: 10.1111/scs.12529
|View full text |Cite
|
Sign up to set email alerts
|

Father group leaders' experiences of creating an arena for father support – A qualitative study

Abstract: The father group leaders described how participants often have high education levels and orderly social circumstances. The leaders described that the groups increased the fathers' reflection about parenthood, which could benefit the whole family in both the short and long term. The father group leaders reported that some of the topics in the sessions directly influenced fathers to discuss issues regarding equality and their co-parenting relationship. They also argued that participating in father groups might h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…According to the literature, some men in parent groups feel that they lack sessions that focus explicitly on the father’s role ( Kerstis et al, 2017 ). This criticism did not arise in the study here, where it was evident that the health professionals were sufficiently good at relating to the father’s role whenever the subject arose naturally during the various course sessions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the literature, some men in parent groups feel that they lack sessions that focus explicitly on the father’s role ( Kerstis et al, 2017 ). This criticism did not arise in the study here, where it was evident that the health professionals were sufficiently good at relating to the father’s role whenever the subject arose naturally during the various course sessions.…”
Section: Resultsmentioning
confidence: 99%
“…They emphasized that they could speak more freely when their partner was not present and that they appreciated this moment of “gender segregation” during the family course. Fathers were also asked if they would consider taking part in fathers’ groups, as studies identify that these are a good way to provide support and to ensure that the focus is on topics that are relevant to fathers (Friedewald et al, 2005; Kerstis et al, 2017). A few of the fathers interviewed thought this was a good idea, but most of them did not find the idea of fathers’ groups in the least bit appealing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Allport et al believed that innovative ways to reach father involvement in children's lives are currently under investigation, including use of mobile technologies show promise in effectively engaging fathers and improving family health [36]. Kerstis et al in Sweden showed that participating in father groups (parental classes) might help convince fathers to take more parental leave and build stronger relationships with their partner and child [37]. Adeleye and Okonkwo indicated a significant increase in knowledge and a meaningful change in attitude of men about the role of fathers in preventing maternal death through education via lectures and leaflets [20].…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that to ensure men get the correct support, services should be adapted to their needs (Englar-Carlson, Evans, & Duffy, 2014;Kingerlee et al, 2019). The benefits and experiences of male-only support groups for some father populations are evident in the current literature (Glynn & Dale, 2015;Kerstis, Wells, & Andersson, 2018). However, the benefit of this form of support for fathers of children with DDD is largely unknown and there appears to be a lack of formal evaluation of male-only groups for this population within the current research literature.…”
mentioning
confidence: 99%